REVITALISASI KEARIFAN LOKAL MELALUI PENGOLAHAN RIMPANG SEGAR MENJADI JAMU TRADISIONAL SEBAGAI RINTISAN BISNIS ONLINE - Maromon, Eltina Agustina; Rupidara, Anggreini D.N.; Djawang, Jofret U.S Peku (Jurnal Abdi Insani, 2024)
The revitalization of local wisdom through the processing of various types of rhizomes by housewives in Oelnasi village into traditional herbal medicine/drinks has good potential for development. Housewives and village women do not have knowledge about this. The high level of health problems but the community's minimal purchasing power for chemical medicines from pharmacies due to constraints due to the family's economic incapacity has become an urgency for housewives and village women to be skilled at processing rhizomes into herbal medicines. This activity aims to increase the knowledge of Oelnasi village women regarding the properties of rhizomes, skills in selecting rhizome types, processing management, hygiene of herbal medicine products with the opportunity to become a permanent business so that marketing can be done online. The methods used in implementing training are: (1) consolidation with partners; (2) lecture; (3) mentoring; (4) evaluation through giving questionnaires to training participants regarding the implementation of activities based on LIKERT with the aim of knowing the results of activities that are measured qualitatively. The results of PKM activities show that partners are able to select good quality types of rhizomes, are able to process rhizomes into herbal medicine by implementing hygiene protocols during the production period, and are able to market herbal medicine products via social media (Facebook, TikTok and WhatsApp) using existing devices. The marketing of herbal medicine products processed by partners has been marketed through these three social media, however this has only reached a percentage of 50% because 6 out of 12 partner members are still not digitally literate on social media. Partners produce herbal medicine, market it using digital platforms, but this is not yet optimal due to constraints on human resources, motivation, family and community support.